Jenis, Potensi Dan Nilai Ekonomi Hasil Hutan yang dimanaantkan Masyarakat Sekitar Tahura Bukit Barisan (Studi Kasus: Desa Dolat Rayat Kecamatan Dolat Rayat dan Desa Kuta Rayat Kecamatan Naman Teran) - Dapot Parasian Siagian (Program studi Kehutanan USU, 2012)
DAPOT PARASIAN SIAGIAN: Type, Potency And Economic Value Result of Exploited Forest result by Society in Tahura Bukit Barisan Range ( Case Study Countryside Dolat Rayat and Countryside Kuta Rayat Sub-Province Karo), guided by Oding Affandi, S.Hut, MP And Ir. Liliek Asmono. Forest products can be divided into two, namely timber and non-timber forest products. Timber forest products are various types of wood and processed. Meanwhile, non-timber forest products are various forms of goods or services obtained from forests than non-timber forest products. Pursuant to result of interview with responder, type result of exploited by forest society around TAHURA area is Petung bamboo , Tali bamboo, decorative crop, animal, firewood, humus, and tree seed. The biggest Economics value at Countryside Dolat Rayat is decorative crop exploiting equal to 55,1271% and at Kuta Rayat countryside is bamboo exploiting equal to 60.1709%. Whereas contribution result of forest to economic earnings of Countryside Dolat Rayat is 46% economic earnings contribution outside result of forest equal to 54%. And at Countryside Kuta Rayat earnings contribution economic from result of forest equal to 51% while earnings outside result of forest equal to 49 %. Keyword : Tahura, type, potency, contribution